Innovative steam methane reforming for coproducing CO‐free hydrogen and syngas in proton conducting membrane reactor. Issue 11 (13th August 2019) - Xia, Xiaoliang; Zhou, Hangyue; Zhang, Yan; Jiang, Heqing
Abstract: Steam methane reforming (SMR) is a commercial process to produce syngas. Normally, the as‐produced syngas is characterized by a H2 /CO ratio of 3. However, such H2 /CO ratio is unsuitable for Fischer–Tropsch synthesis. The hydrogen obtained by subsequent upgrading of syngas usually contains residual CO, which readily deactivates Pt electrocatalysts in fuel cells. Here we report an innovative route by coupling SMR with H2 removal in a proton conducting membrane reactor to coproduce syngas with a preferable H2 /CO ratio of 2 and CO‐free H2 on opposite sides of the membrane, which can be directly used for Fischer–Tropsch synthesis and fuel cells, respectively. Notably, H2 is in‐situ extracted by the membrane that only allows the permeation of H2 as protons through the oxide lattice with infinite selectivity, and thus the obtained H2 is CO‐free. This work could provide an alternative option in one‐step conversion of methane into two inherently separated valuable chemicals.